2017
DOI: 10.1037/dev0000402
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in preschoolers and maternal depressive symptoms: An evaluation of mother- and child-driven effects.

Abstract: Child sleep problems are associated with maternal depressive symptoms. It is unclear to what extent the association is due to direct effects or common risk factors for mother and child. Direct effects could represent child-driven processes, where child sleep problems influence maternal depressive symptoms, or mother-driven processes, where maternal depressive symptoms influence child sleep problems. Common factors could be shared genetic and familial environmental risk. Child- and mother-driven processes are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 71 publications
2
16
0
1
Order By: Relevance
“…Our results were similar to those in a previous study that showed that maternal depression can have a direct influence on the infant's sleep pattern especially in the post-partum period [54]. In addition, a study assessing sleep disorder in children and maternal depression showed that maternal depression can be influenced by child sleeping problem [55]. In fact, children were shown to be highly aware of their mother's emotions; this can lead to excess worrying at bedtime and can predispose to disturbance in sleeping patterns [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were similar to those in a previous study that showed that maternal depression can have a direct influence on the infant's sleep pattern especially in the post-partum period [54]. In addition, a study assessing sleep disorder in children and maternal depression showed that maternal depression can be influenced by child sleeping problem [55]. In fact, children were shown to be highly aware of their mother's emotions; this can lead to excess worrying at bedtime and can predispose to disturbance in sleeping patterns [12].…”
Section: Discussionsupporting
confidence: 91%
“…Maternal depression has been extensively studied, and is described as a public health concern, given the high prevalence of depression among mothers especially during the postpartum period [53], and the negative impact maternal depression can leave on the emotional and cognitive development of the child [54,55]. We showed in our study, that maternal depression was associated with sleep disturbance in children.…”
Section: Discussionsupporting
confidence: 53%
“…Also, this study adds to previous research on the adverse effects of mother's prenatal depression on infant development (e.g., Figueiredo, Pinto, Pacheco, & Field, 2017; Gentile, 2017; Stein et al., 2014), by reporting the adverse effects on infant's sleep problems. In their turn, infant's sleep problems may contribute to the emergence of mother's postpartum anxiety and depression symptoms (Ystrom, Nilsen, Hysing, Sivertsen, & Ystrom, 2017), which may help to explain the association between mother's prenatal and postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
“…В нутрисемейное общение -основное условие развития ребенка, важнейший фактор формирования личности, один из главных видов деятельности человека (A.G. Asmolov [1], N.T. Malberg [22], H. Ystrom etc [36]). процесс воспитания и развития ребёнка.…”
Section: Introductionunclassified